2022
DOI: 10.48550/arxiv.2206.05384
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Entanglement Phase Transition Induced by the Non-Hermitian Skin Effect

Abstract: Recent years have seen remarkable development in open quantum systems effectively described by non-Hermitian Hamiltonians. A unique feature of non-Hermitian topological systems is the skin effect, which is the anomalous localization of an extensive number of eigenstates driven by nonreciprocal dissipation. Despite its significance for non-Hermitian topological phases, the relevance of the skin effect to quantum entanglement and critical phenomena has remained unclear. Here, we find that the skin effect induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 173 publications
(365 reference statements)
1
2
0
Order By: Relevance
“…The above results imply that as the non-unitary effect gets larger, the entanglement growth gets reduced. This is analogous to the measurement-induced phase transition [120][121][122] and the entanglement transition in non-hermitian systems [123]. This suggests that our time-dependent solution with the EOW brane with a ghost field may be a gravity dual of an open quantum system where a quantum system evolves in a non-unitary way derived by e.g.…”
Section: Jhep03(2023)105supporting
confidence: 59%
“…The above results imply that as the non-unitary effect gets larger, the entanglement growth gets reduced. This is analogous to the measurement-induced phase transition [120][121][122] and the entanglement transition in non-hermitian systems [123]. This suggests that our time-dependent solution with the EOW brane with a ghost field may be a gravity dual of an open quantum system where a quantum system evolves in a non-unitary way derived by e.g.…”
Section: Jhep03(2023)105supporting
confidence: 59%
“…This approach can provide a theoretical understanding of the various phases and their transitions while uncovering the rich interplay of non-equilibrium many-body physics and topology [67]. As reported in recent studies, entanglement entropy and entanglement dynamics can act as an important diagnostic tools which reveal the topological signatures of a non-Hermitian many-body systems [287][288][289][290].…”
Section: Nesss and Many-body Phases In Non-hermitian Systemsmentioning
confidence: 88%
“…shown that the entanglement dynamics of monitored free fermions display a subtle behavior, with transitions and crossovers between phases with sub-extensive scaling [30,32,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. This phenomenon was quantitatively understood only very recently, exploiting a mapping to effective non-linear-sigma-model field theories [34,[55][56][57], see also [33].…”
Section: Introductionmentioning
confidence: 99%